Development of Interactive Multimedia of Dayak Mualang Pinggan Dance to Support Continuing Education - Istiandini, Winda (EDUTEC : Journal of Education And Technology, 2024)
Conventional learning models that lack multimedia components have made the learning process less engaging. This issue arises from the evolving mindset of children in accordance with technological advancements, which necessitates the integration of innovative products in educational settings. This research focuses on the importance of multimedia in teaching dance, leading to the development of interactive multimedia for traditional local dance material, specifically Pinggan dance. The research modifies Borg and Gall’s development procedure to fit the context of time and location, involving stages such as information gathering, initial product preparation, expert evaluation, large group trials, product revisions, small group trials, and final product formulation. The subjects of the study included art teachers, tenth-grade students of SMAN 3 Pontianak, and three experts. Data from expert reviews and field trials indicated several product revisions, including script amendments, filming techniques, and multimedia display enhancements. The final product is an interactive multimedia application in Adobe Flash format, featuring dance movement tutorials, make-up and costume guides, accompanying music, dance props, and stage preparation for Pinggan dance.